Floral species richness, structural diversity and conservation value of vanilla agroecosystems in Madagascar. (17th July 2019) - Hending, Daniel; Andrianiaina, Angelo; Maxfield, Pete; Rakotomalala, Zafimahery; Cotton, Sam
Abstract: Agricultural landscapes provide financial livelihoods for farming communities in rural areas. However, such agroenvironments can significantly impact the local floral biodiversity and introduce harmful invasive species to the ecosystem. Despite the prominence of plantations throughout the tropics, their effects on local flora are limited to only a few specific cash crops and geographical regions. Here, we compared the species richness and structural diversity of vegetation in natural forest fragments and three types of vanilla plantation within the Sava region of north‐east Madagascar ranging from those within or adjacent to existing forests, to intensively cultivated plantations. We recorded data on plant species abundance, diameter at breast height and canopy cover within multiple sites of each habitat. We used abundance data to calculate species richness indices, and we compared these metrics between habitats. Forested habitats contained a significantly higher floral species richness, structural diversity and more endemic and regionally native species than nonforested, anthropogenic vanilla plantations. However, our results suggest that the high floral species richness and structural diversity of natural forests can be partially achieved in vanilla plantations, depending on the site's management regime; traditionally managed vanilla plantations located close to natural forests can support diverse floral communities. These encouraging findings for plant conservation and sustainable agroforestry in Madagascar suggest that that newly created vanilla plantations and already existing nonforested plantations should endeavour to follow the more traditional forested approach to enhance the future sustainability and promote floristic diversity. Résumé: Les paysages agricoles fournissent des moyens de subsistance financiers aux communautés agricoles des zones rurales. Cependant, de tels agroenvironnements peuvent avoir un impact significatif sur la biodiversité florale locale et introduire des espèces envahissantes nuisibles dans l'écosystème. Malgré l'importance des plantations à travers les tropiques, leurs effets sur la flore locale sont limités à quelques cultures commerciales et régions géographiques spécifiques. Ici, nous avons comparé la richesse en espèces et la diversité structurelle de la végétation dans des fragments de forêt naturelle et trois types de plantations de vanille dans la région de Sava au nord‐est de Madagascar, allant de celles situées à l'intérieur ou à proximité de forêts existantes à des plantations intensivement cultivées. Nous avons enregistré des données sur l'abondance des espèces de plantes, le diamètre à la hauteur de la poitrine et le couvert forestier dans plusieurs sites de chaque habitat. Nous avons utilisé les données d'abondance pour calculer les indices de richesse des espèces et nous avons comparé ces mesures entre les habitats. Les habitats forestiers contenaient une richesse d'espèces florales significativement plus élevée, une diversité structurelle et des espèces plus endémiques et indigènes que les plantations de vanille anthropiques non forestières. Cependant, nos résultats suggèrent que la richesse élevée des espèces florales et la diversité structurelle des forêts naturelles peuvent être partiellement réalisées dans les plantations de vanille, en fonction du régime de gestion du site; les plantations de vanille gérées de manière traditionnelle situées à proximité de forêts naturelles peuvent accueillir diverses communautés florales. Ces résultats encourageants pour la conservation des plantes et l'agroforesterie durable à Madagascar suggèrent que les plantations de vanille nouvellement créées et les plantations non forestières existantes devraient s'efforcer de suivre l'approche plus traditionnelle des forêts pour améliorer la durabilité et promouvoir la diversité floristique.